IN WHAT PROPORTIONS TO SEMI-ARID AGROECOSYSTEMS AND PRODUCTION SYSTEMS MODIFY THE BROMATOLOGY OF THE ‘GIGANTE’ CACTUS PEAR? (Nativa, 2024)
ABSTRACT: Edaphoclimatic conditions of agroecosystems, genotypic characteristics of the plant and the management system can modify the nutritional quality of cactus pears (Opuntia ficus-indica Mill). This work evaluated the influence of agroecosystems and production systems on the bromatological composition of cactus pear cladodes. Five agroecosystems were studied: 1 - Irrigated District of Ceraíma, Guanambi-BA (14° 17’ 40” S; 42° 42’ 44” W); 2 – Iuiu Valley, Iuiu-BA (14° 23’ 50” S; 43° 27’ 07” W); 3 - Maniaçu, Caetité-BA (13° 48’ 50” S; 42° 24’ 32” W); 4 - Baixio, Riacho de Santana-BA (13° 32’ 08” S; 43° 09’ 19” W); 5 - Morrinhos, Guanambi-BA (14° 14’ 02” S; 42° 37’ 08” W). Cactus pear tissue samples were collected from August to September 2017. A hierarchical design was used: plant plots were arranged in three repetitions at each cactus pear production system, represented by four farms within five agroecosystems, totaling 20 properties of traditional growers. The bromatological variables most affected by the agroecosystem were organic matter and ash in the cladodes. The production systems adopted by the traditional cactus pear growers affected most of the contents of dry matter, nitrogen, crude protein, and neutral detergent fiber. Plant genotype influenced the composition of neutral detergent fiber of the cladodes to a greater extent.Keywords: environment; forage quality; Cactaceae; cropping systems. Agroecossistemas do Semiárido e sistemas de produção modificam a bromatologia da palma forrageira ‘Gigante’ - em quais proporções? RESUMO: As condições edafoclimáticas dos agroecossistemas de cultivo, características genotípicas da planta e o sistema de manejo adotado podem alterar a qualidade nutricional da palma forrageira. Este trabalho avaliou a influência dos agroecossistemas e sistemas de produção na composição bromatológica dos cladódios da palma forrageira (Opuntia ficus-indica Mill). Foram estudados cinco agroecossistemas: 1 - Distrito Irrigado de Ceraíma, Guanambi-BA (14° 17’ 40” S; 42° 42’ 44” O); 2 - Vale do Iuiu, Iuiu-BA (14° 23’ 50” S; 43° 27’ 07” O); 3 - Maniaçu, Caetité-BA (13° 48’ 50” S; 42° 24’ 32” O); 4 - Baixio, Riacho de Santana-BA (13° 32’ 08” S; 43° 09’ 19” O); 5 - Morrinhos, Guanambi-BA (14° 14’ 02” S; 42° 37’ 08” O). A coleta dos tecidos da palma forrageira foi realizada de agosto a setembro de 2017. Utilizou-se o delineamento hierárquico, com as parcelas de plantas dispostas em três repetições dentro do fator sistemas de produção de palma forrageira representado por quatro propriedades, dentro de cinco agroecossistemas, totalizando 20 propriedades de produtores tradicionais. As variáveis bromatológicas mais afetadas pelo agroecossistema de cultivo correspondem aos teores de matéria orgânica e do material mineral na planta. Os sistemas de produção adotados pelos produtores tradicionais de palma forrageira afetaram mais os níveis de matéria seca, nitrogênio, proteína bruta e fibra em detergente neutro. O genótipo da planta influenciou em maior proporção a composição da fibra em detergente neutro dos cladódios.Palavras-chave: ambiente; qualidade da forragem; Cactaceae; sistemas de produção.